Comparison Analysis of The Performance of Financial Reports on Conventional Bank and Islamic Bank - Asta, Sephia Septiana; Hasan, Zulfikar; Kamiludin, Kamiludin (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2023)
The existence of many bank financial institutions in Indonesia makes the whole community and the government feel the impact of the existence of banks. From the past until now, all economic activities in Indonesia have depended on bank financial institutions. With the current dual banking system, it is difficult for the public to determine which bank is more effective as a financial institution that can be trusted to have good quality and financial performance. This study aims to find out how the performance of financial statements is compared between conventional banks (BRI) and Islamic banks (BSI) for 2021 – 2022. The method used in this research is a descriptive qualitative method. The results obtained from this study show that the financial performance of BRI banks in 2021 – 2022 is superior in evaluating the ratios of ROA, ROE, and LDR compared to BSI banks. However, BSI banks are superior to BRI banks in assessing the NPL ratio. Even so, there are advantages between the two banks, which have a good and effective soundness. The contribution that can be made from the results of this research is in the form of a comparison with similar research. The hope is that sharia banking can play a sharia economic role in Indonesia, which has the power of having the most immense Muslim majority in the world.